Clostridial strain degeneration: new approaches to an old problem - Humphreys, Jonathan Richard (2019)
The genus Clostridium comprises a range of physiologically diverse species including notorious pathogens as well as industrially relevant organisms. Solventogenic Clostridia produce solvents via their unique acetone-butanol-ethanol (ABE) fermentation metabolism and encompass species of significance for future biofuel production. Typically these organisms undergo an initial acidogenic phase which is followed by a solventogenic phase as they enter stationary growth. The later phase also sees a morphological change in these organisms as they accumulate storage compounds and endospores. With an increased need for sustainable fuel production, solventogenic Clostridia offer an attractive alternative to produce biobutanol. An intrinsic problem with these organisms however is the phenomenon of spontaneous strain degeneration. This phenomenon is characterised by a reduced or complete loss in the production of solvents and the formation of spores which typically occurs when the bacteria are repeatedly subcultured in batch culture or grown in continuous fermentations.